PRACTICAL ASPECTS OF MAINTAINING THE INTERNATIONAL STANDARD OF ACCOUNTING FOR RESERVES, CONTINGENT LIABILITIES AND CONTINGENT ASSETS (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
This article delves into the practical implications of the International Accounting Standard (IAS) pertaining to reserves, contingent liabilities, and contingent assets. It explores how businesses can effectively apply these standards to ensure transparent financial reporting, manage risks, and make informed decisions. Practical examples and guidelines are provided to assist organizations in navigating the complexities associated with these accounting principles.